AHMADIYAH AND THE FREEDOM OF RELIGION IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2009)
This article analyzes the violence and Joint Ministerial Decree against Jamaah Ahmadiyah Indonesia (JAI), especially relating to freedom of religion. It argues that Indonesia has ratified the International Covenant of Civil and Political Rights (ICCPR) which guarantees the freedom of religion. In addition, Indonesia has also passed laws regarding the freedom of religion such as those in the 1945 constitution. However, these legal foundations have failed to guarantee freedom of religion in Indonesia. The violence against JAI is the proof of this Not only did the government let the incidents occur, but it also issued a Joint Ministerial Decree condemning the activities of JAI. The situation was exacerbated by the fatwa> of the Council of Indonesian `Ulama’ (MUI) which led to more attacks against JAI throughout the country. The article finds that the issuance of the decree was not based on need or legal basis but was an attempt to please radical groups in society.